CREATION OF A POLYMER TOOL IN THE FORM OF A FUNGICIDAL CREAM - KACHAN, ROMAN; KURNOSOV, DMITRY; ZHOVNIR, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper shows the expediency of creating a polymer composite material in the form of a cream with fungicidal properties. This will allow you to get a product that will combine several properties - wound-healing and fungicidal. Such properties are very valuable in the treatment of fungal skin infectionsNowadays, there is a rapid spread of various types of mycoses. Mycosis of the skin is no exception. They are mainly caused by pathogenic fungi. At first, there may be small red spots and slight itching locally, if left untreated, mycosis spreads to the entire skin of the body and nails. On the skin, causative agents of mycosis form wounds over time. As a result, the patient loses quality of life. In addition, mycoses can also spread to other organs. Treatment of mycosis of the skin with systemic drugs is an effective method, but it can cause a toxic effect on the patient's body. Therefore, it is important to create local remedies that can be used in the treatment of this disease. Most often, the following forms of local remedies are used for the treatment of mycosis of the skin: creams, ointments, solutions. Cream is the optimal form. The cream is easily applied to the skin, does not run off, does not stain clothes. Also, thanks to its balanced composition, wounds heal. Therefore, a cream was chosen as the basis of a topical agent with a fungicidal effect. In addition to the usual components of the cosmetic cream, urea, panthenol and a fungicidal agent are added to the cream with a fungicidal effect. Urea moisturizes the skin, enhances the fungicidal effect, panthenol has a regenerating effect. Two types of creams with the same base and different fungicidal agents were obtained. In the first, pyrithione zinc was used as an active substance, in the second, a mixture of four QAK. Using the agar diffusion method, it was established that these creams with these active substances have a pronounced fungicidal effect on the main pathogens of mycoses.
Keywords: cream with fungicidal effect; regenerating properties; panthenol